HA-Med: A Blockchain-Based Solution for Sharing Medical Data with Hidden Policies and Attributes - Xiaohui Yang; Jing Liu (IET Information Security)
Existing healthcare data-sharing solutions often combine attribute-based encryption techniques with blockchain technology to achieve fine-grained access control. However, the transparency of blockchain technology may introduce potential risks of exposing access structures and user attributes. To address these concerns, this paper proposes a novel healthcare data-sharing scheme called HA-Med. By leveraging blockchain technology, HA-Med ensures the concealment of access policies and attributes, providing a secure solution for fine-grained access control of medical data. Furthermore, the scheme supports attribute revocation and forward secrecy to enhance user privacy. The security of HA-Med is rigorously verified through theoretical analysis, and its feasibility is demonstrated through experiments conducted using the Java-based JPBC library.